Konseling Kelompok Rasional Emosi Perilaku dalam Meningkatkan Penyesuian Diri Peserta Didik Pasca Pandemi Covid-19 - Pratiwi, Rahmanida Puerna; Prayogi, Fiki; Suri, Dharlinda (Lentera: Jurnal Ilmiah Kependidikan, 2022)
This research was motivated by the low level of self-adjustment of students after the Covid-19 pandemic which was characterized by a lack of concern for friends, feeling inferior to friends, lack of socializing with friends and unable to work together. The purpose of this study was to find out the effectiveness of REP group counseling services to improve students' self-adjustment after the Covid-19 pandemic. The method used in this research is an experimental method with a quasi-experimental form with the type of one group pre-test-post-test design. The research population consisted of 30 students with a sample of 8 students. The sampling technique used is purposive sampling. Data collection uses a self-adjustment scale. Data analysis used paired sample T test. Statistical test results were obtained at a value (sig) ≤0.000 <0.05 and Z count -30,453 > Z table 1.860. This is indicated by the acquisition of an average pre-test score of 73.87 and a post-test score of 124.38. This value indicates an increase in the average score before and after being given group counseling services with the REP approach with an average difference of 50.51 so that the hypothesis is accepted and it can be concluded that group counseling services are effective on students' self-adjustment to the REP approach